Impact of Community Service on Happiness and Health of Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The aim of this research was to ascertain whether or not there is a relationship between the quantity of community service that teenagers engage in and the degree of happiness and mental health that they characterise for themselves. As part of this study effort, we sought to find out how teens' level of community service involvement related to various measures of their happiness and mental health. A total of 100 teenagers—56 men and 44 women—were chosen from different parts of Indore, Madhya Pradesh, using the snowball sampling technique. Fifty of them participated in community service, while the other fifty did not. Participants in the research were given a range of questionnaires, including a demographic survey, the Oxford Happiness Questionnaire, and the Mental Health Questionnaire. An individual's emotional and psychological well-being is positively impacted by volunteering, according to the results of a research using Pearson correlation. Additionally, compared to their classmates who did not participate in the program, teenagers who performed community service reported noticeably greater levels of happiness and mental health, as shown by independent sample t-tests. The results show that community service has a beneficial influence on teenagers' emotional and mental health, indicating that it might be a useful way to help young people.